PENGARUH DISIPLIN KERJA DALAM MEDIASI HUBUNGAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA - Tegor Tegor; Said Nuwrun Thasimmim; Eka Langgeng Dianasari; Yusmalina Yusmalina (JURNAL CAFETARIA, 2023)
This study aims to see the influence of work discipline in mediating the relationship between the work environment and employee job satisfaction in the Regional Tax and Levy Management Agency (BPPRD) Batam city. The number of respondents used as samples in this study was as many as 70 civil servants. The results showed that: (1) The work environment has a positive and significant effect on the discipline of work in the Regional Tax and Levy Management Agency of Batam City, seen from the value of t values 184,194, (2) The work environment has a positive and significant effect on employee job satisfaction in the Tax and Levy Management Agency of Batam City with a value of t values of 21,699, (3) Work discipline has a positive and significant effect on employee job satisfaction in the Regional Tax and Levy Management Agency (BPPRD) Batam city with the value of t values amounting to 6,480, (4) The work environment positively and significantly affects the job satisfaction of employees in the Batam Regional Tax and Levy Management Agency mediated by the work discipline with a value of T values of 190,674.